Organizational commitment of workers in a public university in Lima and its relationship with demographic variables - Loli Pineda, Alejandro E. (2006)
The present investigation tries to know the organizational commitment about the workers not teachers of a public university of Lima and its relation with some demographic variables in a sample of 205 people of a whole of 20 faculties. The results throw a suitable trend of the workers towards the organizational commitment and the analysis of the factors indicates very significant and positive correlation between general satisfaction with the work and work commitment, affective commitment, hierarchy of the position and permanency feeling; whereas, the relation between the first one and the commitment of convenience is very significant but negative. The same happens between the commitment with the work and commitment of convenience. Also we find very significant and positive association between the commitment with the work and the affective commitment, permanency feeling and hierarchy of the position. In the mean while, the demographic variables with regard to the organizational commitment throws no relation; but separated analysis for each one of the organizational commitment factors allows to find important relation with education, antiquity in the university, antiquity in the current position and current position. Other demographic variables such as sex, age, labour conditions, marital status and workers’ number, though they show trends of commitment in some cases are not changeable statistically variables.